IMAGE DETECTION EDGE IMAGE USING CANNY EDGE ALGORITHM - Damanik, Romanus (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2022)
In general, edge detection is widely used in image processing to find the boundaries of objects in an image. In this study, a technique for detecting edges that is commonly used will be studied, namely the Canny method under different conditions using Visual Studio software. In the testing process that the author carried out, it was concluded that sooner or later a process of converting an object would be, that the following factors affect the conversion process, including; type of image, image resolution, image format, specifications of the camera used to take pictures as well as the specifications of a computer that has a processing speed that is expected to be able to process images (images). The use of the Canny method to detect the edges of an image is considered more accurate and effective because this method is able to provide detailed output by including a calculated execution time